Balita ISPA di Lingkungan Batu Bata - Kamali Zaman; Muhamadiah Muhamadiah; Winda Septiani (Jurnal Kesehatan Komunitas, 2022)
Acute Respiratory Tract Infection (ISPA) is still the dominant factor in patient visits to the puskesmas as a primary health care unit. The phenomenon of the incidence of ISPA caused by multiple factors is a challenge for health workers. Environmental factors are often considered elements that do not have a major role in the incidence of ISPA cases. Ironically, environmental factors have also been neglected in the effort to handle ISPA cases. Candirejo village is an area with the economic characteristics of the community as a producer of bricks. This study aims to see the relationship between ISPA with independent variables (dust, occupancy density, house ventilation, lighting and humidity). This research is quantitative with a cross sectional design in order to see the environmental and physical factors of the house on the incidence of ISPA in toddlers. This study took a sample of 100 households with children under five. This research is expected to be a new evidence related to environmental and physical factors of the house on the incidence of ISPA in toddlers. Variables that are significantly related to the incidence of ARI are house ventilation and residential density variables. The study found that humidity as a confounding factor. The results of the analysis obtained that the OR of the house ventilation variable that did not meet the requirements would cause the occurrence of ISPA in children under five at 16 times more risk than the ventilation of the house that met the requirements after controlling for the humidity variable.  It is suggested to the puskesmas through sanitarian staff to carry out Information Communication and Education (KIE) activities about ISPA during the posyandu implementation.